PRODUCTION OF HYPERIMMUNE SERUM AGAINST ANTHRAX - Umuraliyev, B.K.; Seisenbayeva, M.S.; Zhakypbek, A.S.; Rsaliev, A.S.; Isakhan, A.A.; Orazymbetova, N.K.; Kaukarbayeva, M.ZH.; Zhugunisov, K.D.; Kondibayeva, Zh.B.; Koshemetov, Zh.K; Abduraimov, E.O. (Eurasian Journal of Applied Biotechnology, 2025)
This study presents the results of obtaining a specific hyperimmune serum against the causative agent of anthrax (Bacillus anthracis). As antigenic material, purified and inactivated strains “STI-1”, “78/NIIPBB”, and “Anthrax culture (matrix No. 71, Tsienkovsky’s second vaccine)” were used. To accelerate the production of specific antibodies, various hyperimmunization schemes were tested using sheep, goats, and rabbits. Immunization was carried out with adjuvants of different origins — complete Freund’s adjuvant, aluminum hydroxide, and Montanide ISA-70 — at an antigen-to-adjuvant ratio of 1:1. The dynamics of antibody titer increase were evaluated using diffusion precipitation and indirect hemagglutination assays. It was found that the highest antibody titers were observed in goats and rabbits on the 21st day after immunization, reaching 1:2560, indicating a pronounced immune response when combined antigen administration schemes were applied. The results confirm the efficiency of selecting an optimal hyperimmunization strategy and demonstrate the feasibility of using small laboratory and farm animals for producing specific hyperimmune sera against Bacillus anthracis. These findings provide a foundation for developing rapid and cost-effective methods for the production of specific serum preparations.